Estudo de sintomas musculoesqueléticos, fatores de risco e exposição física em trabalhadores de escritório - Barbieri, Dechristian França (Universidade Federal de São Carlos, 2013)
The high incidence of musculoskeletal disorders (WRMD) among computer workers can be associated with different risk factors such as psychosocial, organizational and ergonomic. The worker s satisfaction with his/her job, workload, and the demand and control relationship are the main psychosocial risk factors. Although these factors are not predictive of WRMD, they can act together with ergonomic factors and can stand out when biomechanical stress is absent. When considering biomechanical factors, the literature reports the low muscular rest combined to the low variation in activation. The knowledge available in the literature does not support an effective method of intervention to prevent WRMD in subjects doing intensive computer work. Considering the available hypotheses regarding the nature of WRMD in intensive computer workers, it is suggested that the enrichment of work by different tasks that introduce variation to the physical exposure of these workers can improve musculoskeletal health. This variation could reduce the risk of WRMD. However, it is not known if in fact physical exposure of computer workers varies according to such tasks. A recent study comparing muscle activity (EMG) during computer and non-computer work showed that EMG did not effectively changed across the tasks. However, the study has not evaluated movements, and the identification of tasks was based on software. In order to contribute with information on the mechanisms of exposure in office workers performing intensive use of the computer during work, two studies were developed and compose this dissertation. The Study 1 compared ergonomics and psychosocial indicators between office workers characterized as symptomatic and asymptomatic. Forty-two office workers that use the computer at least 5 years at work have participated. Subjects were divided into two groups according to the results of the Nordic Musculoskeletal Questionnaire (NMQ). Subjects who have experienced any upper limb and neck symptom during the last week were labeled as symptomatic subject (SS). Subjects that have not reported symptoms in these body parts in the last 7 days were classified as asymptomatic subjects (AS). The Utrecht Work Engagement Scale (UWES) and Job Content Questionnaire (JCQ) were used to measure psychosocial indicators. Ergonomic Workplace Analysis (EWA) was used as with ergonomics indicator. The results showed higher annual and weekly prevalence of discomfort in the wrist/hand region. The UWES demonstrated that SS have less work engagement. The groups have also differed according to the workspace and job content, according to EWA. Therefore, SS differed from AS regarding both ergonomics and psychosocial factors. In order to obtain more precise information about the risk of this population developing WRMD the Study 2 was developed. The objective was to elucidate if the exposure in non-computer tasks is substantially different from exposure in computer work. Fifty servants (11 male and 39 female), selected according to the same criteria as the previous study, participated of the study. Bilateral EMG of upper trapezius (UT) and wrist extensor (WE), as well as movements of the head, neck, upper back and shoulder were recorded during 2 hours. The tasks performed during the recordings were timed. All data were then concatenated into: Task 1 computer work (CW); Task 2 seated non-computer work (NCW-seat); Task 3 stand non-computer work (NCW-stand); Task 4 - pauses (NC-pauses). Variables that characterize physical exposure were calculated and compared using the Friedman test and alpha level at 5%. Additionally, the contrast between CW and the others tasks was calculated as an indicator of exposure. In general, the results showed that during CW the average EMG of UT was lower, there was less variability in activation, larger and more variable relative rest time - RRT in relation to the other three tasks. The non-dominant WE did not have the same response to the different tasks. On the other hand, the dominant WE presented lower average EMG in CW versus NCW-stand and lower variability (SD and CV) in CW versus the others tasks. Data of movements showed similar results, whit lower amplitude recorded during CW. I general, NCW-stand showed more difference when comparing average data with CW. The data of contrast were consistent with EMG data and movements. The best values were observed when contrasting CW versus NCW-stand. In conclusion, non-computer work performed in upright position showed higher physical demand by considering both EMG and movement data. Therefore, it is possible to suggest that this task can potentially increase variability in physical exposure of computer workers. However, this information still need to be more investigated in order to generate clear and practical recommendations.
Keywords: Fisioterapia; LER/DORT; Movimento; Ergonomia; Eletromiografia; Análise de movimento; Aspectos psicossociais; WRMD; Ergonomics; Electromyography; Movement analysis; Psychological aspects; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL